USE OF TECHNOGENIC RAW MATERIALS FOR THE PRODUCTION OF CERAMIC BUILDING MATERIALS - SUBBOTA ІRYNA; SPASONOVA, LARYSA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Despite the difficult times in the world and in Ukraine, construction and architecture are developing every year, and the need for environmentally friendly and efficient materials is growing. One of the directions of ceramic building materials production development is the use of man-made raw materials that solve environmental issues. The use of metallurgical waste in the production of building materials allows you to create new materials, study their properties and behavior in certain operating conditions. Waste generated during metallurgical production, used in the production technology of building materials, helps to reduce the influence on the environment. The integration of waste into production allows to reduce dependence on traditional raw materials and helps to reduce the costs of materials, as well as energy resources. The paper presents the results of research of ceramic masses based on the clay of the Kyiv deposit with the use of metallurgical production waste. Two-component mixtures containing clay and 10, 20 and 30% of metallurgical slag were studied. Ceramic samples were prepared by the method of plastic molding, using a technological mode as close as possible to the process of manufacturing ceramic products for construction purposes. Brick with the addition of slag has better physical and mechanical properties, such as increased strength, crack resistance and reduced shrinkage, which makes it more attractive for construction. The water absorption and strength of bricks made with 30% addition of metallurgical waste have improved significantly − water absorption decreased by 2.0 times when fired at 1000 °C, which affects durability and quality. The flexural strength increased more than 2 times when fired at both 950 °C and 1000 °C, while the compressive strength increased almost 3 times at these firing temperatures. The use of metallurgical waste has been shown to reduce the shrinkage of bricks during drying and firing, which leads to a reduced risk of cracking and deformation, which in own turn can reduce the cost of repair and replacement of materials. Lower costs of raw materials and energy contribute to lower prices for final products, making building materials more competitive. Due to the limitation of high-quality clay raw materials in many regions of our country, the possibility of using local low-melting clays for the production of building ceramics has been presented. The addition of metallurgical production waste to the slurry will allow to expand the use of local raw materials for efficient and environmentally friendly production of construction ceramics and improve the environmental situation in the regions of metallurgical production.